Sugarcane Bagasse Saccharification by Enzymatic Hydrolysis Using Endocellulase and β-glucosidase Immobilized on Different Supports - Morais Júnior, Wilson Galvão (2021)
The saccharification of sugarcane bagasse by enzymatic hydrolysis is one of the most promising processes for obtaining fermentable sugar to be used in the production of second-generation ethanol. The objective of this work was to study the immobilization and stabilization of two commercial enzymes: Endocellulase (E-CELBA) in dextran coated iron oxide magnetic nanoparticles activated with aldehyde groups (DIOMNP) and β-glucosidase (E-BGOSPC) in glyoxyl agarose (GLA) so that their immobilized derivatives could be applied in the saccharification of pretreated sugarcane bagasse. This was the first time that the pretreated sugarcane bagasse was saccharified by cascade reaction using a endocellulase immobilized on dextran coated Fe2O3 with aldehyde groups combined with a β-glucosidase immobilized on glyoxyl agarose. Both enzymes were successfully immobilized (more than 60% after reduction with sodium borohydride) and presented higher thermal stability than free enzymes at 60, 70, and 80 °C. The enzymatic hydrolysis of the sugarcane bagasse was carried out with 15 U of each enzyme per gram of bagasse in a solid-liquid ratio of 1:20 for 48 h at 50 °C. Under these conditions, 39.06 ± 1.18% of the cellulose present in the pretreated bagasse was hydrolyzed, producing 14.11 ± 0.47 g/L of reducing sugars (94.54% glucose). In addition, DIOMNP endo-cellulase derivative maintained 61.40 ± 1.17% of its enzymatic activity after seven reuse cycles, and GLA β-glucosidase derivative maintained up to 58.20 ± 1.55% of its enzymatic activity after nine reuse cycles.